2018
DOI: 10.2169/internalmedicine.0793-18
|View full text |Cite
|
Sign up to set email alerts
|

Disease Exacerbation after the Cessation of Fingolimod Treatment in Japanese Patients with Multiple Sclerosis

Abstract: Objective In Japan, following the launch of dimethyl fumarate (DMF) after fingolimod as a disease-modifying drug in multiple sclerosis (MS), some patients switched from fingolimod to DMF. The aim of this study was to determine the follow-up status of MS patients who switched to DMF after fingolimod cessation. Methods Clinical and magnetic resonance imaging (MRI) data in 19 patients with MS who switched to DMF were collected for at least for 6 months after fingolimod cessation. Results Ten patients (52.6%) expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Reported cases of unexpected increases in clinical and MRI activity after discontinuation of fingolimod began accumulating in 2012 [10,[25][26][27][28][29][30][31][32][33][34][35], with some including reports of tumefactive lesions on MRI [36][37][38][39][40]. While these cases exhibit a significant amount of clinical heterogeneity, a recently published case series has demonstrated three different MRI patterns of post-fingolimod rebound: tumefactive lesions, a punctated pattern with innumerable small T2 and gadolinium (Gd)enhancing lesions, and a pattern more typical of classical MS [40].…”
Section: Reports Of Disease Rebound After Fingolimod Discontinuationmentioning
confidence: 99%
“…Reported cases of unexpected increases in clinical and MRI activity after discontinuation of fingolimod began accumulating in 2012 [10,[25][26][27][28][29][30][31][32][33][34][35], with some including reports of tumefactive lesions on MRI [36][37][38][39][40]. While these cases exhibit a significant amount of clinical heterogeneity, a recently published case series has demonstrated three different MRI patterns of post-fingolimod rebound: tumefactive lesions, a punctated pattern with innumerable small T2 and gadolinium (Gd)enhancing lesions, and a pattern more typical of classical MS [40].…”
Section: Reports Of Disease Rebound After Fingolimod Discontinuationmentioning
confidence: 99%
“…In contrast, cases of severe MS rebound after fingolimod withdrawal have recently been reported . A recent study also reported that 10 of 19 Japanese MS patients who switched fingolimod to DMF showed clinical or radiological exacerbation, and three of these 10 patients developed multifocal tumefactive lesions . Patients with high disease activity before fingolimod treatment might be predisposed to severe rebound syndrome .…”
Section: Discussionmentioning
confidence: 99%
“…Fingolimod rebound syndrome has been reported in a growing number of case series, [3][4][5][6][7][8][9][10][11][12][13][14][15][16] and there were three case series composed of a relatively large number of patients. 3,15,16 In the three studies, the prevalence of fingolimod rebound syndrome ranged from 5 to 53%, although the study whose prevalence was 53% included radiological exacerbation. Rebound syndrome emerged from 3 to 12 weeks after drug cessation, and lymphocyte counts at the rebound ranged from 300 to 2100 (/mm 3 ), elevated from those during the fingolimod treatment.…”
Section: Discussionmentioning
confidence: 99%